Typification of the name Hoodia currorii (Apocynaceae) - Figueiredo, Estrela; Smith, Gideon F. (Phytotaxa, 2019)
Hoodia currorii Decaisne (1844: 665) is a well-known species of carrion flower from west-central Namibia and southern Angola. Bruyns et al. (2017) reclassified more than 30 stapeliad genera in an enlarged concept of Ceropegia Linnaeus (1753: 211). This resulted in Ceropegia consisting of over 750 species, one of which being then referred to as ‘C. currorii (Hook.) Bruyns’ (2017: 420), based on Scytanthus currorii Hooker (1844: 605). This species of carrion flower is nowadays most widely included in the genus Hoodia Sweet ex Decaisne (1844: 664), and we here treat it as H. currorii. The citation of the author of H. currorii and the citation of its type have been the source of some confusion in the literature and are here clarified.